Transfusion-transmitted malaria: case report of asymptomatic donor harboring Plasmodium malariae - Patricia Scuracchio; Sergio Domingos Vieira; Denise Albuquerque Dourado; Luciana Moro Bueno; Rafael Colella; Eduardo Milton Ramos-Sanchez; Giselle F. M. Castro Lima; Juliana Inoue; Maria Carmen Arroyo Sanchez; Silvia Maria Di Santi (Revista do Instituto de Medicina Tropical de São Paulo, 2011)
Malaria in Brazil is endemic in the Amazon region, but autochthonous cases with low parasitaemia occur in the Atlantic Forest area of the country. According to Brazilian legislation no test is mandatory for blood donors from non-endemic areas. However if they have traveled to malaria transmission regions they are deferred for six months before they can donate. This report describes a transfusion-transmitted malaria case in Sao Paulo, Brazil, where one recipient received infected blood and developed the disease. He lived in Sao Paulo and had no previous transfusion or trips to endemic areas, including those of low endemicity, such as Atlantic Forest. Thick blood smears confirmed Plasmodiummalariae. All donors lived in Sao Paulo and one of them (Donor 045-0) showed positive hemoscopy and PCR. This asymptomatic donor had traveled to Juquia, in the Atlantic Forest area of S ao Paulo State, where sporadic cases of autochthonous malaria are described. DNA assay revealed P. malariae in the donor's (Donor 045-0) blood. Serum archives of the recipient and of all blood donors were analyzed by ELISA using both P. vivax and P. falciparum antigens, and IFAT with P. malariae. Donor 045-0's serum was P. malariae IFAT positive and the P. vivax ELISA was reactive. In addition, two out of 44 donors' archive sera were also P. vivax ELISA reactive. All sera were P. falciparum ELISA negative. This case suggests the need of reviewing donor selection criteria and deferral strategies to prevent possible cases of transfusion-transmitted malaria.